DNA Topoisomerases and Cancer - Pommier, Yves.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
DNA topoisomerases are present in all living organisms and are essential to maintaining the helical structure of DNA. They are highly relevant for cancer because a number of anti-cancer drugs selectively target two of the human enzymes, DNA topoisomerases I and II. Those drugs convert topoisomerases into cellular poisons by trapping the enzymes as they cleave DNA. The book starts out with a detailed outline of the phyllogeny of the different topoisomerases, continues with recent studies on the crystal structures of the human topoisomerases, and their biochemistry. The following section reviews the chemical biology of the topoisomerase inhibitors used in cancer chemotherapy and the implication of topoisomerases in generating recombinations and DNA damage. The third section summarizes the current use of the various topoisomerase inhibitors in cancer chemotherapy. And finally, the last section includes several chapters describing the DNA repair pathways for topoisomerase-induced DNA damage. This book is intended for students and faculty but also for health care professionals who wish to have a self-contained and up-to-date information on topoisomerases. Chapters have been written by leaders and world reknowned experts in the topoisomerase field.
Introduction and Historical Perspective -- Human DNA topoisomerase I: Structure, Enzymology and Biology -- Mitochondrial topoisomerases -- Structure and mechanism of eukaryotic type IIA topoisomerases -- Essential functions of topoisomerase III in the nucleus and mitochondria -- DNA topoisomerase I and illegitimate recombination -- Topoisomerase-induced DNA damage -- Topoisomerases and carcinogenesis: Topo III and BLM -- Topoisomerase inhibitors: a paradigm for interfacial inhibitors -- Topoisomerase I inhibitors: chemical biology -- Topoisomerase II inhibitors: chemical biology -- Topoisomerase I inhibitors: current use and prospects -- Topoisomerase II inhibitors: current use and prospects -- Transcription stress by camptothecin: mechanism and implication for the drug antitumor activity -- Mechanism regulating cellular responses to DNA topoisomerase I-targeted agents -- Tyrosyl-DNA-phosphodiesterase -- Ubiquitin and ubiquitin-like proteins in repair of topoisomerase-mediated DNA damage -- Repair of topoisomerase II-mediated DNA damage: fixing DNA damage arising from a protein covalently trapped on DNA -- Topoisomerases and Apoptosis -- Index.
Keywords: Medicine; Cancer research; Pharmacology; Biomedicine; Cancer Research; Pharmacology/Toxicology.; Electronic books